2016
DOI: 10.1126/scitranslmed.aaf6594
|View full text |Cite
|
Sign up to set email alerts
|

Global health partnerships: Are they working?

Abstract: An assessment of global health collaborations highlights the advantages of synergies between global health research and training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…These observations and priorities are consistent with past surveys of global health leaders and their partners. 2 The process of conference planning and partner engagement is consistent with published recommendations for an approach to global health partnerships. 3,4 Notable aspects of the DGHI Partnership Conference included bringing partners from 14 different sites to a host institution with a breadth of intellectual disciplines across the university and including the medical center.…”
Section: Discussionsupporting
confidence: 55%
“…These observations and priorities are consistent with past surveys of global health leaders and their partners. 2 The process of conference planning and partner engagement is consistent with published recommendations for an approach to global health partnerships. 3,4 Notable aspects of the DGHI Partnership Conference included bringing partners from 14 different sites to a host institution with a breadth of intellectual disciplines across the university and including the medical center.…”
Section: Discussionsupporting
confidence: 55%
“…21 Recent surveys of university and pediatric residency program partnerships demonstrate the centrality of research, education, clinical care, health systems strengthening, health interventions, policy development, and technology exchange. 7,22 Educational activities may involve a unidirectional or bidirectional exchange of health professionals, undergraduate, or postgraduate learners. 22,23 Some relationships are built around short-term GCH experiences for trainees.…”
Section: Genesis Evolution and Scope Of Gch Partnershipsmentioning
confidence: 99%
“…7,22 Educational activities may involve a unidirectional or bidirectional exchange of health professionals, undergraduate, or postgraduate learners. 22,23 Some relationships are built around short-term GCH experiences for trainees. These are often unidirectional flows of learners from HICs to LMIC that provide questionable benefit to LMIC institutions.…”
Section: Genesis Evolution and Scope Of Gch Partnershipsmentioning
confidence: 99%
“…10,11 Further, studies have identified that key process factors such as establishing mutual goals, establishing project oversight, monitoring, feedback, and communication are required for successful implementation of global health partnerships. 12 However, there is an important evidence gap regarding why certain global partnerships work while others fail. [13][14][15][16] This study explored global health partnerships in continuing medical education to understand how interactions between individual players in different contexts influence the outcomes of these partnerships.…”
Section: Introductionmentioning
confidence: 99%
“…Chua et al 42 Case report Indonesia Bilateral Singapore HIV None found 12 Sherer et al 43 Case report China Bilateral United States HIV Zhao et al 44…”
mentioning
confidence: 99%